Effect of recitation method on mathematical reasoning ability and student self confidence - Mohammad Dadan Sundawan; Toto Nusantara; Subanji Subanji; Erry Hidayanto (Universitas PGRI Madiun, 2023)
Mathematics is one of the basic sciences that has an important role in the world of education. In general, the purpose of learning mathematics is to help students prepare themselves to be able to face changing circumstances in life and in an ever-evolving world, through practicing acting on the basis of logical, rational and critical thinking and preparing students to be able to use mathematics and a mathematical mindset. in everyday life and in studying various sciences. The aims of this study were (1) to determine the effect of the use of the recitation method on the mathematical reasoning abilities of grade VI elementary school students; (2) to determine the effect of using the recitation method on the self-confidence of VI elementary students. The method that researchers used in this study was quasi-experimental (quasi-experimental). Sampling in this study using purposive sampling technique, while for data analysis researchers used the normality test, homogeneity test, correlation analysis, simple linear regression analysis and t test. The results showed that there is an effect of the recitation method on students' mathematical reasoning abilities of 19.7% and the average value of mathematical reasoning abilities in the experimental class is better than the average value of mathematical reasoning abilities in the control class. There is an effect of the recitation method on students' self-confidence of 51.2%.